A review of universal design and accessibility legislations in implementation strategies among Asian countries - Abd Samad, Nur Amira; Said, Ismail; Abdul Rahim, Asiah (Universitas Gadjah Mada, 2018)
What distinguishes the rights of Person with Disabilities (PwDs) in gaining access to the built environment, is Accessibility and equal participation in the society, is discrimination. It was a remarkable legal instrument for PwDs in Asian countries when UNCRPD responded in being concern that the existing human rights instruments have not given significant impact on the improvement of PwDs’ quality of life. Accessibility legislation between Malaysia, Singapore, Thailand and Japan has different success rate when it comes to implementing and enforcing Universal Design via legislative and regulatory documents, government initiatives and planning approach. The success rate of implementation for Accessibility, are different from developed and developing countries even within Asian regions despite the movement started around the same time. The results are derived from content analysis of reviews chronologically and thematically at all four countries. Therefore, a brief discussion elaborated by comparing those countries of developed and developing and to conclude, signifying causes of success or the setbacks of implementation efforts.